Global identification and analysis of isozyme-specific possible substrates crosslinked by transglutaminases using substrate peptides in mouse liver fibrosis - Tatsukawa, Hideki (Sci Rep, 2017)
The transglutaminase (TG) family comprises eight isozymes that form the isopeptide bonds between glutamine and lysine residues and contribute to the fibrotic diseases via crosslinking-mediated stabilization of ECM and the activation of TGF-β in several tissues. However, despite a growing body of evidence implicating TG2 as a key enzyme in fibrosis, the causative role of TG2 and the involvement of the other isozymes have not yet been fully elucidated. Therefore, here we clarified the distributions of TG isozymes and their in situ activities and identified the isozyme-specific possible substrates for both TG1 and TG2 using their substrate peptides in mouse fibrotic liver. We found that TG1 activity was markedly enhanced intracellularly over a widespread area, whereas TG2 activity increased in the extracellular space. In total, 43 and 42 possible substrates were identified for TG1 and TG2, respectively, as involved in chromatin organization and cellular component morphogenesis. These included keratin 18, a biomarker for hepatic injury, which was accumulated in the fibrotic liver and showed the partly similar distribution with TG1 activity. These findings suggest that TG1 activity may be involved in the functional modification of intracellular proteins, whereas TG2 activity contributes to the stabilization of extracellular proteins during liver fibrosis.